HUBUNGAN ANTARA KESEPIAN DAN KETERLIBATAN AYAH PADA REMAJA - Sutanto, Sandra Handayani; Suwartono, Christiany (Konsorsium Psikologi Ilmiah Nusantara (KPIN), 2019)
Abstract - Apart from the noise and spark of the city, loneliness is often still engulfing teenagers. Previous research found that relationships with peers and parents were predictors of loneliness experienced by adolescents. However, no study has specifically examined parental involvement, especially father involvement. This study also aims to reveal the participation of fathers in parenting with loneliness in adolescents. This research is a quantitative study using a measurement tool adaptation from the UCLA Loneliness Scale and Father Involvement Scale. The sample size of this study was 189 adolescents by convenience sampling technique. The results showed that most teenagers felt lonely but were not related to father involvement in their lives. Discussion of the study tried to elaborate on the factors of location for data collection, developmental stages, and habits of adolescents. The results of the additional analysis showed that female adolescents tended to experience loneliness compared to male adolescents. Suggestions for research are given to get a more comprehensive picture of the phenomenon of loneliness in adolescents. Also, practical advice is also given to reduce loneliness in young women. Abstrak - Terlepas dari keramaian perkotaan, kesepian masih melanda para remaja. Penelitian sebelumnya menemukan bahwa relasi dengan teman sebaya dan orang tua merupakan prediktor dari kesepian yang dialami remaja. Namun, belum ada penelitian yang secara khusus meneliti keterlibatan orang tua, terutama keterlibatan ayah. Penelitian ini bertujuan untuk mengetahui partisipasi ayah dalam pengasuhan dan hubungannya terhadap kesepian remaja. Studi survei kuantitatif ini menggunakan UCLA Loneliness Scale dan Father Involvement Scale, pada 189 remaja. Hasil menunjukkan hampir sebagian besar remaja merasakan kesepian, namun tidak berhubungan dengan keterlibatan ayah dalam kehidupan mereka. Hasil analisa tambahan menunjukkan bahwa remaja perempuan cenderung mengalami kesepian dibandingkan remaja laki-laki. Diskusi penelitian mencoba mengelaborasi faktor lokasi pengambilan data, tahapan perkembangan, dan kebiasaan remaja yang memengaruhi hasil.